(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
In the last years, many works demonstrated the possibility to directly interact with the epigenetic signature of an adult mature cell, through the use of epigenetic modifiers, (Pennarossa et al., 2013; Brevini et al., 2014, Chandrakantan et al., 2016) and new mechanisms underlying this process have been recently described (Manzoni et al., 2016). In particular, the small molecule 5-azacytidine (5-aza-CR) has been shown to induce a transient higher plasticity state in adult somatic cells, grown in standard 2D conditions. Recent evidence have also shown the possibility to regulate and maintain cell pluripotency through the use of 3D culture systems. In the experiments here presented, we combine the two approaches and investigate whether the simultaneous use of a 3D micro-bioreactor and 5-aza-CR is able to promote cell rearrangement, boost the induction of high plasticity and stably maintain it. To this purpose, fibroblasts were either plated on plastic dishes (2D) or encapsulated in a Liquid Marble (LM) micro-bioreactor (polytetrafluoroethylene (PTFE)), which has been previously shown to support the growth of living microorganisms, tumor spheroids, fibroblasts, red blood cells, and embryonic stem cells (Ledda et al., 2016). Cells were then erased with 5-aza-CR, for 18 hours and cultured in Embryonic Stem Cell (ESC) medium for up to 28 days. Morphological analysis and pluripotency related gene expression levels were monitored for the entire length of the experiments. 2D cells, kept a monolayer pattern and acquired a pluripotent state that was, however, transient and lost by day 6. In contrast the use of a 3D system maintained and stabilized the high plasticity state in LM cells until the end of the experiments (Fig. 1). The data obtained demonstrate that cell rearrangement and interactions may modulate 5-aza-CR induced plasticity and suggest a correlation between 3D mechano-transduction-related pathways and epigenetic regulation of cell phenotype.